Use of glenoid inclination angle for the assessment of unilateral congenital high scapula. Issue 1 (January 2016) - Nakamura, Naoyuki; Inaba, Yutaka; Machida, Jiro; Saito, Tomoyuki
Abstract : Little has been reported on the motion of the scapula in Sprengel's deformity. Fourteen patients with unilateral congenital high scapula underwent the Woodward procedure from 1986 to 2004. The median age of the patients at the time of surgery was 4.4 years and the median follow-up duration was 8.8 years. The range of motion of the shoulder and the glenoid inclination angle (GIA) were measured preoperatively and at the final visit. The range of motion of the shoulder and GIA improved at the final visit. There was a positive correlation between the maximum abduction angle of the upper limb and GIA at the final visit.